2005
DOI: 10.1152/ajpregu.00417.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular actions of rattlesnake bradykinin ([Val1,Thr6]bradykinin) in the anesthetized South American rattlesnakeCrotalus durissus terrificus

Abstract: actions of rattlesnake bradykinin ([Val 1 ,Thr 6 ]bradykinin) in the anesthetized South American rattlesnake Crotalus durissus terrificus. Am J Physiol Regul Integr Comp Physiol 288: R456 -R465, 2005. First published October 21, 2004; doi:10.1152/ajpregu.00417.2004.-Incubation of heat-denatured plasma from the rattlesnake Crotalus atrox with trypsin generated a bradykinin (BK) that contained two amino acid substitutions (Arg 1 3 Val and Ser 6 3 Thr) compared with mammalian BK. Bolus intra-arterial injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…5, 28); however, vagal tone is normally low or even absent in reptiles anesthetized with barbiturates (e.g., Refs. 10,16). Furthermore, because the hypoxic responses persisted after muscarinic receptor blockade by atropine in caimans (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…5, 28); however, vagal tone is normally low or even absent in reptiles anesthetized with barbiturates (e.g., Refs. 10,16). Furthermore, because the hypoxic responses persisted after muscarinic receptor blockade by atropine in caimans (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The rattlesnake and the tegu lizard have undivided ventricles and, consequently, equal pressures in systemic and pulmonary circulation (Ref. 16; N. Skovgaard and T. Wang, unpublished observations on tegus). Their lungs are unicameral with a central air-filled cavity that opens radially into the parenchyma (26,32).…”
Section: Hpv In Reptilesmentioning
confidence: 99%
See 2 more Smart Citations
“…In reptiles, activity in the vagal innervation of the pulmonary artery can massively reduce G pul and increased vagal tone can mediate large net R-L shunts (Burggren 1987;Luckhardt and Carlson 1921;Milsom et al 1977;Taylor et al 2009). Adrenergic control of systemic conductance (G sys ) may alter blood flow relations (Hicks 1994;Galli et al 2007), and many humoral factors such as nitric oxide (Crossley et al 2000;Galli et al 2005a), bradykinin (Galli et al 2005b) and adenosine (Joyce and Wang 2014) have also been demonstrated to affect cardiac shunt patterns. Thus, as the relative importance of central regulation of cardiac shunt patterns through vagal innervation of the pulmonary artery remains uncertain, it is pertinent to re-evaluate whether the vagus accounts for significant changes in cardiac shunts to respond to alterations in metabolic demand in conscious organisms.…”
Section: Introductionmentioning
confidence: 99%